2003
DOI: 10.1038/nrm1129
|View full text |Cite
|
Sign up to set email alerts
|

Killing the messenger: short RNAs that silence gene expression

Abstract: Short interfering RNAs can be used to silence gene expression in a sequence-specific manner in a process that is known as RNA interference. The application of RNA interference in mammals has the potential to allow the systematic analysis of gene expression and holds the possibility of therapeutic gene silencing. Much of the promise of RNA interference will depend on the recent advances in short-RNA-based silencing technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
714
1
10

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,063 publications
(730 citation statements)
references
References 112 publications
5
714
1
10
Order By: Relevance
“…30 The suppression of oncogenic N-Ras in melanoma cells harboring this mutation did not appear to be entirely specific, as siRNA directed at WT NRAS in cells harboring only mutant NRAS also resulted in a small reduction (25%) in N-Ras expression. Furthermore, we observed that targeting WT NRAS using siRNA directed at oncogenic NRAS resulted in decreased N-Ras expression in melanoma cells with only WT NRAS alleles.…”
Section: Discussionmentioning
confidence: 97%
“…30 The suppression of oncogenic N-Ras in melanoma cells harboring this mutation did not appear to be entirely specific, as siRNA directed at WT NRAS in cells harboring only mutant NRAS also resulted in a small reduction (25%) in N-Ras expression. Furthermore, we observed that targeting WT NRAS using siRNA directed at oncogenic NRAS resulted in decreased N-Ras expression in melanoma cells with only WT NRAS alleles.…”
Section: Discussionmentioning
confidence: 97%
“…There is currently substantial hope that RNA interference (RNAi)-mediated modulation of protein expression can be used for prevention or treatment of diseases, 1 but only a few studies in whole animals have been reported so far. Here, we show that transgenic expression of a short hairpin (sh) RNA targeting Bim efficiently prevents the development of polycystic kidney disease in Bcl-2-deficient mice and that this effect can be transmitted over several generations.…”
Section: Dear Editormentioning
confidence: 99%
“…The mechanism of RNAi is that the short double-stranded (ds) RNA can mediate the degradation of sequence specific mRNA [38][39][40] . It has been reported that introducing small interfering RNAs (siRNAs) or short hairpin RNA (shRNA) into mammalian cells could specifically silence the expression of target genes [41][42][43] .…”
Section: Introductionmentioning
confidence: 99%